Hämophilie-Patienten in Deutschland 2008/2009 - Schramm, W.; Krebs, H.; für teilnehmenden Behandlungseinrichtungen (Hämostaseologie, 2010)
Since 1978 an annual multicentric survey regarding the epidemiology of patients suffering of haemophilia is performed with support of hemophilia treating centres of any size. Again the actual compilation is resting upon a broad database returning to over 30 years of inquiry well representing both the actual and retrospective status of mortality. Prompted was exclusively information about patients with haemo philia A, B and von Willebrand disease. In particular anonymous data concerning the last 12 months about number of treated patients, type and severity of illness, HIV-status and detailed information about causes of death was inquired. This data was merged with existing data and analyzed statistically. In the 2008/2009 survey, a total number of 9101 patients with bleeding disorders have been reported from 66 participating centres. Despite mortality from HIV in patients with haemophilia is keeping on decreasing, HIV still remains an important factor as an HIV/HCV coinfection seems to increase risk of progression of severe liver disease. Age structure in our patients has been shifting significantly over the last decades bringing age distribution into line with the entire population. This has to be considered assessing mortality and morbidity.
Keywords: Haemophilia; haemophilia A; haemophilia B; von Willebrand disease; epidemiology; factor VIII; factor IX; morbidity; mortality; cause of death; HIV; AIDS; HCV